HUBUNGAN POWER OTOT LENGAN BAHU DAN KOORDINASI MATA-TANGAN DENGAN HASIL SET SHOT PADA TIM BOLA BASKET PUTRA SMA N PLUS PEKANBARU - Candra, Deni Clara; Ramadi, Ramadi; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Purpose of this research is knowing relation of shoulder arm muscle power and hand-eye coordination with the result of set shot test on male student basketball team of SMA N Plus Pekanbaru. Method in this research is using quantitative method, type of this research is correlation or correlational research. Population is all players in male student basketball team of SMA N Plus Pekanbaru that have 12 members. Sampling technique that been used was total sampling with 12 players. Instrument that been used in this research was “two hand medicine ball put” test, “tennis ball throw and catch” test and “shooting set shot” test. After that data counted with statistic, for examine normality with lilifors test on significant level α (0,05). Hipothesys that submitted is, there is a relation between shoulder arm muscle power and hand-eye coordination with the result of set shot test on male student basketball team of SMA N Plus Pekanbaru. Based on the result of the research and data processing with using statistic procedure have concluded that a significant relation between shoulder arm muscle power and hand-eye coordination with the result of set shot, because rhitung on significant level α (0,05) = 0,602 which is rhitung(0,631) > rtabel(0,602).Keywords: Relation, Shoulder Arm Muscle Power, Hand-Eye Coordination, Set Shot